It is time to reclaim “holistic heart care” - Klug, Eric (SA Heart Journal, 2017)
The theme of the 2010 SA Heart Annual congress was “Holistic Heart Care”. In Greek “holos” means total, entire, all or whole. Holistic health encompasses all aspects of people’s needs: psychological; spiritual; physical; and social. It implies our health system in general and its component parts in particular cannot determine our patient management. It should rather be the patient who should determine how the medical profession cares for them holistically. Conventional medicine seems to have lost claim to the term “holistic care”, a term which is now associated with “alternative medicine” practitioners.